The genus Odontophrynus (Anura: Odontophrynidae): a larval perspective - Nascimento, Filipe Augusto C. Do; Mott, Tamí; Langone, José A.; Davis, Christine A.; de Sá, Rafael O. (Zootaxa, 2013)
The genus Odontophrynus consists of 11 species of medium-sized frogs distributed across south and east South America. This study examines and describes the chondrocrania and oral cavities of O. americanus, O. maisuma, O. carvalhoi, and O. cultripes, and review current knowledge about the larval external morphology of the genus. Twenty-one tadpoles were cleared and double-stained for chondrocranium description and five tadpoles were dissected for analysis in a scanning electron microscope. The presence of a tectum parientale may be considered here as a putative synapomorphy of the genus. The O. americanus and O. cultripes species groups were partially differentiated by the length of the processus pseudopterigoideus, shape of divergence of the hypobranchial plates, number of postnarial papillae, and number of projections of the lateral ridge papillae. The larvae of O. occidentalis species group, in turn, differed from others by presenting a greater total length.